Psychotropic drug prescriptions in Western European nursing homes. (29th July 2016) - Janus, Sarah I. M.; van Manen, Jeannette G.; IJzerman, Maarten J.; Zuidema, Sytse U.
ABSTRACT: Background: Despite the numerous warnings of European and national drug agencies as well as clinical guidelines since the year 2004, psychotropic drugs are still frequently used in dementia. A systematic review comparing the use of psychotropic drugs in nursing homes from different European countries is lacking. Objective: The aim of this study was to examine prescription rates of psychotropic drug use in nursing home patients between different Western European countries since the first warnings were published. Methods: A literature review was performed and the various psychotropic prescribing rates in European nursing homes were investigated. The prescription rates of antipsychotic and antidepressants were pooled per country. Other classes of psychotropic drugs could not be pooled because of the limited number of studies found. Results: Thirty-seven studies on antipsychotic drug use and 27 studies on antidepressant drug use conducted in 12 different European countries. The antipsychotic use in nursing homes ranged from 12% to 59% and antidepressant use from 19% to 68%. The highest rates of antipsychotic drug prescription were found in Austria, Ireland, and Belgium while for antidepressants in Belgium, Sweden, and France. Conclusions: Despite warnings about the side effects and recommendation to focus on non-pharmacological interventions, antipsychotics and antidepressants are commonly used drugs in nursing homes. The data suggest that Norway does best with regards having a low antipsychotic drug usage. Studies are needed to explain the differences between Norway and other European countries.